Sleep Quality and Anxiety Among College Students in West Kalimantan, Indonesia - Triyana Harlia Putri; Djoko Priyono (Jurnal Aisyah : Jurnal Ilmu Kesehatan, 2021)
The purpose of this study was to assess college students’ sleep quality and the prevalence of anxiety in this group. This study was conducted cross-sectionally online and was carried out at universities in the province of West Kalimantan. 663 students were selected as participants through snowball sampling. Instruments used included the General Anxiety Disorder-7 (GAD-7) and the Pittsburgh Sleep Quality Index (PSQI). We found that students had poor sleep quality and high anxiety levels, while of students had good sleep quality but also experienced high levels of anxiety. We also observed a correlation between sleep quality subscales (subjective sleep quality, duration of sleep, sleep latency, disturbance of sleep) and anxiety (p = 0.293, p = 0.182, p = 0.279, p = 0.361). Overall, sleep quality correlated with anxiety (p = 0.735). Sleep quality was significantly associated with academic major (OR = 0.73, 95% CI (0.49, 1.51)) and anxiety was significantly associated with age (OR = 1.139, 95% CI (0.769, 1.68)). Sleep quality and anxiety were significantly correlated in students, and they both correlated with socio-demographic characteristics such as age and academic major. Coping strategies are considered a control point that could help overcome the impact of COVID-19.Tujuan dari penelitian ini adalah untuk menilai kualitas tidur mahasiswa dan prevalensi kecemasan pada kelompok ini. Penelitian ini dilakukan secara cross-sectional secara online dan dilakukan pada perguruan tinggi di provinsi Kalimantan Barat. 663 mahasiswa dipilih sebagai partisipan dengan snowball sampling. Instrumen yang digunakan adalah General Anxiety Disorder-7 (GAD-7) dan Pittsburgh Sleep Quality Index (PSQI). Kami menemukan bahwa mahasiswa memiliki kualitas tidur yang buruk dan tingkat kecemasan yang tinggi, sedangkan mahasiswa yang memiliki kualitas tidur baik tetapi juga mengalami tingkat kecemasan yang tinggi. Kami juga mengamati korelasi antara subskala kualitas tidur (kualitas tidur subjektif, durasi tidur, latensi tidur, gangguan tidur) dan kecemasan (p = 0,293, p = 0,182, p = 0,279, p = 0,361). Secara keseluruhan, kualitas tidur berkorelasi dengan kecemasan (p = 0,735). Kualitas tidur secara signifikan terkait dengan jurusan akademik (OR = 0,73, 95% CI (0,49, 1,51)) dan kecemasan secara signifikan terkait dengan usia (OR = 1,139, 95% CI (0,49, 1,68)). Kualitas tidur dan kecemasan berkorelasi secara signifikan pada mahasiswa, dan keduanya berkorelasi dengan karakteristik sosio-demografis seperti usia dan jurusan akademik. Strategi koping dianggap sebagai titik kontrol yang dapat membantu mengatasi dampak COVID-19